Monitoring Biodiversitas Ikan sebagai Bioindikator Kesehatan Lingkungan di Sekitar Muara Sungai Bian, Kabupaten Merauke - Komberem, Agustinus B; Elviana, Sisca; Sunarni, Sunarni (Nekton, 2022)
The Bian River, the estuary, to the coast, have very high fishery potential. Residents around the river use the Bian River as a source of livelihood and also as a means of transportation that connects one area to another. The purpose of this study was to determine species diversity, the quality of environmental parameters so as to determine environmental health conditions around the Bian River based on the Seawater Quality Standard for marine biota in PP Decree No. 22 of 2021. The results showed that during 2 months of observation, 25 species were found from three stations. Observations, where the most caught species were Metapeneus monoceros and the least species found, were Paraplotosu salbilabris, Paraplagus iabilineata, Gerresoyena, Paraplagus iabilineata. Leviprora inops, Plesio batisdaviesi, Himantura uarnak. The results of water quality measurements of temperature, salinity, dissolved oxygen (DO), and pH still support the presence of marine biota and have not been polluted in a stable category.